1992
DOI: 10.1111/j.1432-1033.1992.tb16966.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the rat pulmonary surfactant protein A promoter

Abstract: The expression of the pulmonary surfactant protein A (SP‐A) is developmentally regulated and controlled by several hormones. In an attempt to characterize cis‐acting elements involved in the regulation of SP‐A expression, we have cloned the 5′ flanking sequence of the rat SP‐A gene. The promoter region contains a TATA box but no CAAT box. The transcription start site has been identified by anchored polymerase chain reaction and S1 nuclease mapping of the mature and precursor transcripts. S1 mapping of precurso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1993
1993
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 48 publications
0
14
0
Order By: Relevance
“…Using a CAT-reporter construct in which the CAT expression is under the control of the SP-D 5 H promoter segment (SP-D698), we examined the effect of RB on the SP-D698 reporter activity in the lung epithelial MLE-15 cells [Wikenheiser et al, 1993]. As shown in Figure 2A, when cotransfected to MLE-15 cells, RB stimulated SP-D698/CAT reporter activity more than three fold, whereas RB had only marginal effect on SP-A236/CAT reporter activity despite the presence of a consensus NF-IL6 binding site (TTCTGCAAT) n the SP-A promoter region (À184/À176) [Lacaze-Masmonteil et al, 1992]. The positive effect of RB on the SP-D698/CAT reporter was also observed in HeLa cells (data not shown).…”
Section: Rb Activates Sp-d Genementioning
confidence: 95%
“…Using a CAT-reporter construct in which the CAT expression is under the control of the SP-D 5 H promoter segment (SP-D698), we examined the effect of RB on the SP-D698 reporter activity in the lung epithelial MLE-15 cells [Wikenheiser et al, 1993]. As shown in Figure 2A, when cotransfected to MLE-15 cells, RB stimulated SP-D698/CAT reporter activity more than three fold, whereas RB had only marginal effect on SP-A236/CAT reporter activity despite the presence of a consensus NF-IL6 binding site (TTCTGCAAT) n the SP-A promoter region (À184/À176) [Lacaze-Masmonteil et al, 1992]. The positive effect of RB on the SP-D698/CAT reporter was also observed in HeLa cells (data not shown).…”
Section: Rb Activates Sp-d Genementioning
confidence: 95%
“…Since there is 95% identity between the amino acid sequence of the SP-As of mouse and rat [23,24], and isolated polyclonal antibodies against rat SP-A [6,25] react with mouse SP-A, the levels of SP-A in BALF of mice were analysed by enzyme-linked immunosorbent assay (ELISA) using monospecific biotinylated and nonbiotinylated antibodies against rat SP-A and mouse SP-A as standards. The levels of cytokines (TNF-a, IL-12, IFN-c, IL-6 and IL-4) in BALF were determined using ELISA kits (BioSource International, Camarillo, CA, USA) according to the manufacturer9s protocol.…”
Section: Surfactant Protein a Cytokine And Immunoglobulin Assaysmentioning
confidence: 99%
“…Recently, sequences for several lung-specific promoters have been obtained, such as those for the lung surfactant proteins A, B, and C and for CC10, a secretory product of airway cells (for a review, see reference 40). Genetic studies using these sequences have begun to provide information on transcriptional regulation in the lung (12,22,25). For example, in situ hybridization in mice and rats has shown that the surfactant protein C gene is expressed exclusively in the alveolar epithelium and the CC10 gene is expressed primarily in the airway, while the surfactant A and B genes are expressed at high levels in both of these locations (12,20,45).…”
mentioning
confidence: 99%